A guanidine-based coronavirus replication inhibitor which targets the nsp15 endoribonuclease and selects for interferon-susceptible mutant viruses. - Benjamin Van Loy; Eugènia Pujol; Kenichi Kamata; Xiao Yin Lee; Nikolai Bakirtzoglou; Ria Van Berwaer; Julie Vandeput; Cato Mestdagh; Leentje Persoons; Brent De Wijngaert; Quinten Goovaerts; Sam Noppen; et al. (PLoS Pathogens)
The approval of COVID-19 vaccines and antiviral drugs has been crucial to end the global health crisis caused by SARS-CoV-2. However, to prepare for future outbreaks from drug-resistant variants and novel zoonotic coronaviruses (CoVs), additional therapeutics with a distinct antiviral mechanism are needed. Here, we report a novel guanidine-substituted diphenylurea compound that suppresses CoV replication by interfering with the uridine-specific endoribonuclease (EndoU) activity of the viral non-structural protein-15 (nsp15). This compound, designated EPB-113, exhibits strong and selective cell culture activity against human coronavirus 229E (HCoV-229E) and also suppresses the replication of SARS-CoV-2. Viruses, selected under EPB-113 pressure, carried resistance sites at or near the catalytic His250 residue of the nsp15-EndoU domain. Although the best-known function of EndoU is to avoid induction of type I interferon (IFN-I) by lowering the levels of viral dsRNA, EPB-113 was found to mainly act via an IFN-independent mechanism, situated during viral RNA synthesis. Using a combination of biophysical and enzymatic assays with the recombinant nsp15 proteins from HCoV-229E and SARS-CoV-2, we discovered that EPB-113 enhances the EndoU cleavage activity of hexameric nsp15, while reducing its thermal stability. This mechanism explains why the virus escapes EPB-113 by acquiring catalytic site mutations which impair compound binding to nsp15 and abolish the EndoU activity. Since the EPB-113-resistant mutant viruses induce high levels of IFN-I and its effectors, they proved unable to replicate in human macrophages and were readily outcompeted by the wild-type virus upon co-infection of human fibroblast cells. Our findings suggest that antiviral targeting of nsp15 can be achieved with a molecule that induces a conformational change in this protein, resulting in higher EndoU activity and impairment of viral RNA synthesis. Based on the appealing mechanism and resistance profile of EPB-113, we conclude that nsp15 is a challenging but highly relevant drug target.